An anti-corrosion preservative for shotcrete and its preparation method and application

By using anti-erosion preservatives prepared from raw materials such as nano-SiO2/perfluorooctyl acrylate composite emulsion and n-decanoic acid in shotcrete, the serious corrosion problem faced by shotcrete in saline soil environments has been solved, and its resistance to corrosion has been significantly improved. Penetration and chloride ion resistance, while reducing the amount of rebound.

CN118908616BActive Publication Date: 2025-01-24SHIJIAZHUANG CHANGAN YUCAI BUILDING MATERIALS +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411405825.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-24
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

During the use of sprayed concrete, spray concrete faces serious material loss, high dust content, poor spray coating quality and insufficient corrosion performance on harmful ions. Especially in saline soil environments, the erosion of sulfate ions and chloride ions leads to concrete. The service life of the structure is shortened.

Method used

Use the in -situ emulsion polymerization nano SiO2/whole fluorinel acrylic composite emulsion, and introduce the hydrococcum aids of positive acid and alcoholine on it to prepare a kind of anti -corrosion preservatives suitable for jet concrete Essence

Benefits of technology

The anti-erosion and anti-corrosion agent significantly improves the anti-permeability, chloride ion resistance and sulfate corrosion resistance of shotcrete, and reduces the amount of rebound without affecting the strength of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908616B_ABST
    Figure CN118908616B_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion preservative for shotcrete and a preparation method and application thereof, and belongs to the technical field of chemical additives for building materials. The preparation method of the anti-corrosion preservative for shotcrete of the invention comprises the following steps: mixing water, n-decanoic acid, ammonia water, and a hydration aid, then adding a nano-SiO2 / perfluorooctyl acrylate composite emulsion, stirring and mixing, and obtaining the anti-corrosion preservative for shotcrete; the hydration aid is triethanolamine, triisopropanolamine, diethanol monoisopropanolamine and diethanolamine in a mass ratio of 4:4:4:2. After adding the anti-corrosion preservative of the invention, the shotcrete can have excellent chloride ion resistance and sulfate erosion resistance, can reduce the rebound of the shotcrete, and will not cause the strength of the concrete to decrease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical additives for building materials, and in particular to an anti-corrosion preservative for shotcrete and a preparation method and application thereof. Background Art

[0002] Since its implementation, shotcrete technology has made great progress in concrete material properties, mix ratio, spraying process improvement, dust control, etc., and has been widely used in tunnel construction, mine support, ground engineering and other fields. However, serious material loss, high dust content on the construction site, and low quality of concrete spraying layer caused by the rebound of fresh concrete during the spraying process are the main challenges facing the industry.

[0003] In addition, shotcrete also needs to consider the service environment and the effect of the use of accelerators on the concrete's resistance to harmful ion corrosion. The deterioration mechanism of concrete caused by environments with high proportions of sulfate ions and chloride ions, such as saline soil environments, is complex, including ion diffusion, chemical reactions, and expansion damage, which will cause corrosion of concrete from the outside to the inside. Chloride ions can reach the surface of the steel bars through the inherent pore network of the concrete protective layer, causing the steel bars to passivate, and then a series of electrochemical reactions will occur, causing steel bar corrosion and concrete expansion and cracking; sulfate ions react with hydrated aluminates in concrete to generate expansion products with low solubility, such as calcium aluminate, which will first fill the pores, further causing the concrete to form microcracks, thereby accelerating the penetration of chloride ions into the concrete. Moreover, in the field of shotcrete, one of the most important materials, the accelerator, the main component of the accelerator is sulfate, and its sulfate content is between 15% and 40%, which means that shotcrete is affected by internal sulfate corrosion at the beginning of its service. In the presence of high concentrations of sulfate both inside the concrete and in the environment, if no effective anti-corrosion measures are taken, bidirectional expansion can easily form through cracks, greatly shortening the service life of the concrete structure. Therefore, for shotcrete, researchers need to consider the different mechanisms of erosion from harmful ions inside and outside; therefore, researching and preparing a concrete anti-corrosion preservative suitable for shotcrete is the key to solving the durability problem of shotcrete. Summary of the invention

[0004] The object of the present invention is to provide an anti-corrosion preservative for shotcrete and its preparation method and application, so as to solve the above-mentioned problems in the background technology. The present invention adopts an in-situ emulsion polymerization method to synthesize a nano-SiO2 / perfluorooctyl acrylate composite emulsion, and on this basis, introduces raw materials such as n-decanoic acid and alcoholamine hydration aids, thereby obtaining an anti-corrosion preservative suitable for shotcrete. After adding the anti-corrosion preservative of the present invention, the shotcrete can have excellent impermeability, chloride ion resistance, and sulfate corrosion resistance, and can reduce the rebound of the shotcrete without causing a decrease in the strength of the concrete.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing an anti-corrosion preservative for shotcrete, comprising the following steps:

[0007] Mix water, n-decanoic acid, ammonia water and a hydration aid, then add nano-SiO2 / perfluorooctyl acrylate composite emulsion, stir and mix, and obtain the anti-corrosion preservative for shotcrete;

[0008] The hydration aids are triethanolamine, triisopropanolamine, diethanol monoisopropanolamine and diethanolamine in a mass ratio of 4:4:4:2.

[0009] Preferably, the preparation method of the nano-SiO2 / perfluorooctyl acrylate composite emulsion comprises the following steps:

[0010] (1) Methyl methacrylate, butyl acrylate and a crosslinking agent are mixed to obtain a core phase monomer; the core phase monomer is placed in an emulsifier aqueous solution to obtain a core monomer pre-emulsion; butyl acrylate, methyl methacrylate and perfluorooctyl acrylate are mixed and placed in an emulsifier aqueous solution to obtain a shell monomer pre-emulsion;

[0011] (2) mixing a buffer, KH550 modified nano-SiO2, an emulsifier aqueous solution and an initiator aqueous solution, and then adding a core phase monomer to obtain a seed emulsion; adding a core monomer pre-emulsion and an initiator aqueous solution to the seed emulsion, reacting, and obtaining a core phase emulsion;

[0012] (3) Adding the shell monomer pre-emulsion and the initiator aqueous solution dropwise into the core phase emulsion to react and obtain a nano-SiO2 / perfluorooctyl acrylate composite emulsion.

[0013] Preferably, the preparation method of the KH550 modified silica is: using tetraethyl orthosilicate as a precursor, preparing nano silicon dioxide (SiO2) by sol-gel method, and in-situ modification with γ-aminopropyltriethoxysilane (KH550). Specifically, 4-6 parts by mass of tetraethyl orthosilicate, 0.5-2 parts by mass of KH550, and 5-8 parts by mass of ammonia water are added to a reactor containing 110-120 parts by mass of anhydrous ethanol, heated to 40-50°C, stirred for 8-12 hours, centrifuged and washed, vacuum dried at 35-40°C until the mass is constant, and ground to obtain KH550 modified nano SiO2.

[0014] There are many active hydroxyl groups on the surface of nano-SiO2. These hydroxyl groups are easy to form hydrogen bonds and to undergo polycondensation reactions with each other. Both of these situations will lead to particle agglomeration. After the Si-OR group on the KH550 silane coupling agent is hydrolyzed, it is adsorbed on the nanoparticles and undergoes polycondensation reactions with the active hydroxyl groups, which can achieve the purpose of end-capping. In addition, the KH550 modification has the following three purposes: (1) changing the polarity of the surface of the SiO2 particles, changing the surface of the SiO2 particles from hydrophilic to hydrophobic, increasing the compatibility with organic solvents and organic monomers, and at the same time utilizing the steric effect of the organic chain segments to stabilize the dispersion of the SiO2 particles; (2) grafting amino functional groups on the surface of the particles, which can form hydrogen bonds or chemical bonds with organic monomers, thereby enhancing the interaction between the SiO2 particles and the organic phase; (3) in the process of atom transfer radical polymerization, the initiator is grafted on the surface of the SiO2 particles, and after reacting with acrylic monomers, it can initiate monomer polymerization, forming a fine special structure with a narrow molecular weight distribution and a high grafting rate on the surface of the SiO2 particles.

[0015] Preferably, the mass ratio of the emulsifier to water in the emulsifier aqueous solution is 3:100, and the emulsifier consists of DNS-86 and OP-10 in a mass ratio of 1-3:0.5-2.

[0016] The emulsifier is a composite emulsifier of anionic emulsifier ammonium ether sulfate (DNS-86) and nonionic emulsifier octylphenol polyoxyethylene ether (OP-10).

[0017] Preferably, the mass ratio of the initiator to water in the initiator aqueous solution is 5:100, and the initiator is one or more of ammonium persulfate, potassium persulfate and sodium persulfate.

[0018] Preferably, in the core monomer pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate and cross-linking agent is 5-10:30-40:2-4; and the cross-linking agent is acrylic acid.

[0019] In the present invention, methyl methacrylate is used as a hard monomer and butyl acrylate is used as a soft monomer.

[0020] Preferably, in the shell monomer pre-emulsion, the mass ratio of the total mass of methyl methacrylate and perfluorooctyl acrylate to butyl acrylate is 2-4:1-2;

[0021] The perfluorooctyl acrylate is one or more of perfluorooctyl ethyl methacrylate, perfluorooctyl ethyl acrylate and perfluorooctanol acrylate.

[0022] Preferably, the step (2) is specifically as follows:

[0023] In a protective atmosphere, 0.1-0.5 parts by weight of a buffer, 5-10 parts by weight of KH550 modified nano-SiO2, an emulsifier aqueous solution and an initiator aqueous solution are mixed, stirred at 80°C at a speed of 100-200 rpm for 20-40 minutes, and then 10 parts by weight of a core phase monomer are added to obtain a seed emulsion; the initiator aqueous solution and a core monomer pre-emulsion are dripped into the seed emulsion, and then the mixture is kept warm at 80°C for 60 minutes to obtain a core phase emulsion; the buffer is sodium bicarbonate.

[0024] Preferably, the step (3) is specifically as follows:

[0025] Add the initiator aqueous solution and the shell monomer pre-emulsion to the core phase emulsion at 80° C., then keep the temperature at 85° C. for 1 hour, adjust the pH value to 8-9, and obtain the nano-SiO2 / perfluorooctyl acrylate composite emulsion.

[0026] Preferably, the mass ratio of the water, n-decanoic acid, ammonia water, hydration aid and nano-SiO2 / perfluorooctyl acrylate composite emulsion is 70:5-10:2-4:2-4:50.

[0027] The hydration aid in the anti-corrosion preservative of the present invention is prepared by combining multiple alcohol amines, and each alcohol amine has different effects on promoting the hydration rate of various components in cement at different ages. The added triethanolamine promotes the early hydration of aluminate, delays the hydration of silicate, improves early strength, and shortens the setting time; triisopropanolamine promotes the hydration of ferrite, which is difficult to hydrate, and improves dispersibility to improve the hydration degree of cement minerals, thereby improving early and late strength. The present invention promotes the hydration of cement at different ages through different alcohol amines, thereby achieving excellent densification and pore sealing effects, and the hydrophobic modification of the pore wall by calcium n-decanoate and nano-SiO2 / perfluorooctyl acrylate composite membrane enables the concrete to achieve better waterproof and anti-seepage effects, and effectively inhibits the penetration of harmful ions into the concrete along with the water medium.

[0028] The second technical solution of the present invention is to provide an anti-corrosion preservative for shotcrete prepared according to the above preparation method.

[0029] The third technical solution of the present invention is to provide an application of the above-mentioned anti-corrosion preservative for shotcrete in the field of improving the durability of shotcrete.

[0030] The beneficial technical effects of the present invention are as follows:

[0031] The present invention adopts an in-situ emulsion polymerization method to synthesize a nano-SiO2 / perfluorooctyl acrylate composite emulsion, and on this basis, introduces raw materials such as n-decanoic acid and an alcoholamine hydration aid, thereby obtaining an anti-corrosion preservative suitable for shotcrete. After adding the anti-corrosion preservative of the present invention, the shotcrete can have excellent chloride ion resistance and sulfate corrosion resistance, can reduce the rebound amount of the shotcrete, and will not cause the strength of the concrete to decrease.

[0032] The anti-corrosion preservative can enhance the cohesion of shotcrete and improve the wrapping of concrete paste in the early stage of use. This is because the nano-SiO2 / perfluorooctyl acrylate composite emulsion particles adsorbed on the surface of cement particles make the surface of cement particles polar. Due to the enhanced repulsion of the same polarity on the surface of cement particles, the flocculent particle structure in the cement solution can be disassembled, but the release of the wrapped water will be slowed down, which is manifested as the concrete fluidity can reach the specified fluidity but the flow rate is slowed down. At the same time, the n-decanoic acid in the raw material reacts with the cement hydration product calcium hydroxide to form calcium n-decanoate, and gradually changes the pore structure during the cement hydration and hardening stage, and finally deposits on the surface of the pore wall of the hardened concrete, blocking the through holes and modifying the pore wall surface, which can play a good hydrophobic performance.

[0033] During the concrete hardening stage, the nano-SiO2 / perfluorooctyl acrylate composite emulsion gradually loses water, the polymer particles form a continuous film, and the perfluoroalkyl (CF 2n-1 ) migrates to the surface of the polymer membrane and spontaneously accumulates at the interface between the membrane and the air, which reduces the surface energy of the membrane and enhances its hydrophobicity, thereby further modifying the pore wall. The alcohol amine in the hydration aid acts as a catalyst for cement hydration reaction, which can significantly improve the early strength of cement, and is also beneficial to the medium and long-term strength of cement, making the cement denser.

[0034] The present invention introduces modified nano silicon dioxide into the polymer system, which can integrate the excellent properties of polymer and inorganic nano materials, so that it not only has the surface effect of nano particles, but also can combine the high rigidity, high strength, dimensional stability, thermal stability and the like of inorganic materials with the toughness of polymer, so that the polymer / inorganic nano composite material has special properties and functions that the original components do not have, so as to improve the properties such as flexibility, thermal stability, corrosion resistance and anti-aging. In addition, due to the unique nano effect of nano particles, when the filling amount is very small, the toughness, strength and heat resistance of the polymer / inorganic nano composite material can be significantly improved. The common problem of the application of organic materials in concrete is that aging brittle cracking occurs with the extension of the service time of concrete, which will affect the stability and durability of the building structure, and the polymer / inorganic nano composite material is more suitable for the hydration heat release high temperature environment of the concrete hardening stage and the service environment under different harsh conditions, which significantly improves the durability of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 Schematic diagram of the core-shell structure of the nano-SiO2 / perfluorooctyl acrylate composite emulsion in Examples 1-5. DETAILED DESCRIPTION

[0037] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0038] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0041] Unless otherwise specified, the parts in the following embodiments and comparative examples of the present invention are all calculated by mass.

[0042] The "room temperature" in the present invention is 10-30°C unless otherwise specified.

[0043] The initiators used in the following examples and comparative examples of the present invention are potassium persulfate and ammonium persulfate in a mass ratio of 4:1. The hydration aids used are triethanolamine, triisopropanolamine, diethanol monoisopropanolamine and diethanolamine in a mass ratio of 4:4:4:2.

[0044] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0045] Example 1

[0046] A method for preparing an anti-corrosion preservative:

[0047] S1: Take 4 parts of tetraethyl orthosilicate, 1 part of KH550, and 6 parts of ammonia water, add them into a reactor filled with 115 parts of anhydrous ethanol, heat to 45°C and stir for 10 hours, centrifuge and wash, vacuum dry at 40°C until the mass is constant, and grind to obtain KH550 modified nano-SiO2.

[0048] S2: DNS-86, OP-10 and deionized water are mixed in a mass ratio of 2.4:1.2:120 to obtain an emulsifier aqueous solution. Initiator and deionized water are mixed in a mass ratio of 5:100 to obtain an initiator aqueous solution. Take 3 parts of acrylic acid, 10 parts of methyl methacrylate and 37 parts of butyl acrylate as core phase monomers, take 40 parts of core phase monomers and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a core monomer pre-emulsion. Weigh 12 parts of butyl acrylate, 24 parts of methyl methacrylate and 15 parts of perfluorooctanol acrylate, mix them evenly and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a shell monomer pre-emulsion.

[0049] S3: Preparation of core phase emulsion: In a four-necked flask equipped with a stirrer, a condenser, a nitrogen introduction device and a dropping funnel, nitrogen is introduced to exclude oxygen, 0.5 parts of sodium bicarbonate and 7 parts of KH550 modified nano-SiO2 are added to 41.2 parts of emulsifier aqueous solution, and 3.5 parts of initiator aqueous solution are added after heating to 80°C, stirred at 150rpm for 30min, 10 parts of core phase monomer are added dropwise, and the addition is completed within 15min, and the temperature is kept for 20min. When blue fluorescence appears, it means that seeds are generated. When the oily reflux of the vessel wall is significantly reduced and the blue color of the liquid in the reaction container is significantly lighter, the seed emulsion is obtained. Use two dropping funnels to synchronously and slowly add 81.2 parts of core monomer pre-emulsion and 3.5 parts of initiator aqueous solution respectively, and the addition is completed within 90min, and continue to be kept at 80°C for about 60min, and the core phase emulsion is obtained.

[0050] S4: Shell polymerization: 92.2 parts of shell monomer pre-emulsion and 3.5 parts of initiator aqueous solution (temperature controlled at about 80°C) were added to the core phase emulsion through two dropping funnels simultaneously and slowly, and the addition was completed over 180 minutes. The temperature was raised to 85°C and kept warm for 60 minutes. After the reaction was completed, the temperature was cooled to room temperature and the pH value was adjusted to 8-9 with aqueous ammonia to obtain a nano-SiO2 / perfluorooctyl acrylate composite emulsion.

[0051] S5: Add 70 parts of tap water into the reactor, heat to 50°C and start stirring at a speed of 35 rpm, add 7 parts of decanoic acid, keep stirring at the temperature for 30 minutes, add 3 parts of ammonia water and keep stirring at the temperature for 45 minutes, add 3.5 parts of hydration aid and keep stirring at the temperature for 30 minutes, turn off the heating, and add 50 parts of nano-SiO2 / perfluorooctyl acrylate composite emulsion after the temperature drops to room temperature to obtain an anti-corrosion preservative.

[0052] Example 2

[0053] A method for preparing an anti-corrosion preservative:

[0054] S1: Same as Example 1.

[0055] S2: DNS-86, OP-10 and deionized water are mixed in a mass ratio of 2.4:1.2:120 to obtain an emulsifier aqueous solution. Initiator and deionized water are mixed in a mass ratio of 5:100 to obtain an initiator aqueous solution. Take 3 parts of acrylic acid, 10 parts of methyl methacrylate and 37 parts of butyl acrylate as core phase monomers, take 40 parts of core phase monomers and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a core monomer pre-emulsion. Weigh 12 parts of butyl acrylate, 24 parts of methyl methacrylate and 10 parts of perfluorooctanol acrylate, mix them evenly and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a shell monomer pre-emulsion.

[0056] S3: Preparation of core phase emulsion: In a four-necked flask equipped with a stirrer, a condenser, a nitrogen introduction device and a dropping funnel, nitrogen is introduced to exclude oxygen, 0.5 parts of sodium bicarbonate and 7 parts of KH550 modified nano-SiO2 are added to 41.2 parts of emulsifier aqueous solution, and 3.15 parts of initiator aqueous solution are added after heating to 80°C, and stirred at 150rpm for 30min, 10 parts of core phase monomer are added dropwise, and the addition is completed in 15min, and the temperature is kept for 20min. When blue fluorescence appears, it means that seeds are generated. When the oily reflux of the vessel wall is significantly reduced and the blue color of the liquid in the reaction container is significantly lighter, the seed emulsion is obtained. Use two dropping funnels to synchronously and slowly add 81.2 parts of core monomer pre-emulsion and 3.15 parts of initiator aqueous solution respectively, and the addition is completed within 90min, and continue to be kept at 80°C for about 60min, and the core phase emulsion is obtained.

[0057] S4: Shell polymerization: 82.2 parts of shell monomer pre-emulsion and 3.15 parts of initiator aqueous solution (temperature controlled at about 80°C) were added to the core phase emulsion through two dropping funnels simultaneously and slowly, and the addition was completed over 180 minutes. The temperature was raised to 85°C and kept warm for 60 minutes. After the reaction was completed, the temperature was cooled to room temperature and the pH value was adjusted to 8-9 with aqueous ammonia to obtain a nano-SiO2 / perfluorooctyl acrylate composite emulsion.

[0058] S5: Same as Example 1.

[0059] Example 3

[0060] The only difference from Example 1 is that step S2 is modified to:

[0061] S2: DNS-86, OP-10 and deionized water are mixed in a mass ratio of 2.4:1.2:120 to obtain an emulsifier aqueous solution. Initiator and deionized water are mixed in a mass ratio of 5:100 to obtain an initiator aqueous solution. Take 3 parts of acrylic acid, 10 parts of methyl methacrylate and 37 parts of butyl acrylate as core phase monomers, take 40 parts of core phase monomers and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a core monomer pre-emulsion. Weigh 12 parts of butyl acrylate, 24 parts of methyl methacrylate and 15 parts of perfluorooctyl ethyl acrylate, mix them evenly and add them dropwise to 41.2 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a shell monomer pre-emulsion.

[0062] Example 4

[0063] The only difference from Example 1 is that step S2 is modified to:

[0064] S2: DNS-86, OP-10 and deionized water are mixed in a mass ratio of 2.4:1.2:120 to obtain an emulsifier aqueous solution. Initiator and deionized water are mixed in a mass ratio of 5:100 to obtain an initiator aqueous solution. Take 3 parts of acrylic acid, 10 parts of methyl methacrylate and 37 parts of butyl acrylate as core phase monomers, take 40 parts of core phase monomers and add them dropwise to 41.6 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a core monomer pre-emulsion. Weigh 12 parts of butyl acrylate, 24 parts of methyl methacrylate and 15 parts of perfluorooctylethyl methacrylate, mix them evenly and add them dropwise to 41.6 parts of emulsifier aqueous solution, stir at high speed at the same time, add the dropwise addition after 0.5h, continue to stir at high speed for 35min, and obtain a shell monomer pre-emulsion.

[0065] Example 5

[0066] The only difference from Example 1 is that step S3 is modified to:

[0067] In a four-necked flask equipped with a stirrer, a condenser, a nitrogen introduction device and a dropping funnel, nitrogen is introduced to exclude oxygen, 0.5 parts of sodium bicarbonate and 10 parts of KH550 modified nano-SiO2 are added to 41.2 parts of an emulsifier aqueous solution, and 3.5 parts of an initiator aqueous solution are added after heating to 80°C, stirred at 150rpm for 30min, 10 parts of a core phase monomer are added dropwise, and the addition is completed within 15min, and the temperature is kept for 20min. When blue fluorescence appears, it means that seeds are produced. When the oily reflux on the wall is significantly reduced and the blue color of the liquid in the reaction container becomes significantly lighter, a seed emulsion is obtained. Use two dropping funnels to synchronously and slowly add 81.2 parts of a core monomer pre-emulsion and 3.5 parts of an initiator aqueous solution, and the addition is completed within 90min, and the temperature is kept at 80°C for about 60min, and a core phase emulsion is obtained.

[0068] Figure 1 Schematic diagram of the core-shell structure of the nano-SiO2 / perfluorooctyl acrylate composite emulsion in Examples 1-5.

[0069] Comparative Example 1

[0070] The nano-SiO2 / perfluorooctyl acrylate composite emulsion in Example 1 is directly used as the final product.

[0071] Comparative Example 2

[0072] A method for preparing an anti-corrosion preservative:

[0073] Add 70 parts of tap water into the reactor, heat to 50°C and start stirring at a speed of 35 rpm, add 7 parts of decanoic acid, keep stirring at the temperature for 30 minutes, add 3 parts of ammonia water and keep stirring at the temperature for 45 minutes, add 2 parts of hydration aid and keep stirring at the temperature for 30 minutes to prepare an anti-corrosion preservative.

[0074] Comparative Example 3

[0075] A method for preparing an anti-corrosion preservative:

[0076] 5 g of silicon dioxide with a particle size of 10 nm was acidified in a 0.01 mol / L hydrochloric acid system, and after the treatment, 1 g of dodecyltriethoxysilane and 1 g of acetic acid were added, and atomization mixing was performed at 120° C. to prepare modified nano-silicon dioxide.

[0077] Add 85g of water, 10g of N-methyldiethanolamine and 0.2g of cellulose ether (molecular weight of 2 million) into the reactor, stir evenly, then add the modified nano-silica to the aqueous solution, control the pH of the solution at 5-9, stir rapidly, and continue stirring until the system is stable after the nano-silica is added to obtain the final product.

[0078] Comparative Example 4

[0079] A rebound regulator is composed of the following components in parts by weight: 1.5 parts of composite modified polyvinyl alcohol, 400 parts of ultrafine mineral powder, 5 parts of sodium silicate, 426.5 parts of calcium-based bentonite, 5 parts of calcium nitrate and 10 parts of sodium hexametaphosphate.

[0080] The preparation method of the composite modified polyvinyl alcohol is:

[0081] S1. In a 250mL three-necked flask equipped with a stirrer, a condenser, and a thermometer, 50mL of vinyl acetate, 3mL of allyl triacetoxysilane, 0.21g of azobisisobutyronitrile, and 10mL of methanol were added respectively, stirring was started, and the temperature was raised to 62±2°C, and the reaction was carried out for 3h; then the temperature was raised to 65±1°C, and the reaction was continued for 0.5h, and then cooled to room temperature; after purification, the mixture was dried at 50°C to obtain silane-modified polyvinyl alcohol; the obtained silane-modified polyvinyl alcohol was dissolved in a 2% by mass aqueous solution of vinyltrimethoxysilane to obtain an intermediate;

[0082] S2. Prepare a 2% mass fraction of vinyl trimethoxysilane aqueous solution, then mix the nano powder SBR with the unsaturated silane aqueous solution, the weight ratio of the nano powder SBR to the unsaturated silane aqueous solution is 1:10, ultrasonically treat for 60 minutes, filter, and dry the filter cake at 100°C; then rinse the filter cake with toluene, centrifuge, and repeat the rinsing and centrifugation 4 times to remove the silane coupling agent self-polymer, to obtain the pretreated nano powder SBR;

[0083] S3. A four-necked flask equipped with an agitator, a dropping funnel and a thermometer is placed in a water bath, and 0.02g of sodium dodecylbenzene sulfonate, 0.3g of NaHCO3 (buffer), 0.01g of K2S2O8, 125mL of water and 2g of the pretreated nano-powder SBR obtained in step S2 are added to the flask; 40g of the silane-modified polyvinyl alcohol obtained in step S1 is added to the dropping funnel, and when the temperature reaches 75°C, the intermediate obtained in step S1 is slowly added dropwise to the flask, and the dropwise addition is completed within 1.5h, and the reaction temperature is then controlled at 75-80°C for 5h; the reaction product is then dried at 80°C to obtain a composite modified polyvinyl alcohol.

[0084] Effect verification

[0085] Examples 1-5 and Comparative Examples 1-4 were respectively added as additives in a solid dosage of 1.2% during the preparation of shotcrete, and the corresponding mixing water was deducted; the formula of the shotcrete is shown in Table 1, wherein the accelerator model is GK-3B (the main component is aluminum sulfate, and the detailed preparation method is shown in patent application CN 202110916790.8), and it meets Q / CR 807-2020 "Liquid alkali-free accelerator for tunnel shotcrete".

[0086] (1) The mechanical properties of the shotcrete prepared by adding the products of Examples 1-5 and Comparative Examples 1-4 were tested according to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50080-2002), and a blank control was made with the shotcrete without adding the anti-corrosion preservative (Blank Group 1). The results are shown in Table 2.

[0087] Table 1 Formula of shotcrete

[0088]

[0089] Table 2 Mechanical properties and rebound rate of shotcrete

[0090]

[0091] It can be found from Table 2 that after Examples 1-5 are used as anti-corrosion preservatives in combination with an accelerator, the 24h strength of the concrete reaches more than 30Mpa, which can improve the early strength of the shotcrete to a certain extent. In addition, the rebound rate data show that the embodiments effectively reduce the rebound rate of the concrete, that is, effectively improve the bonding force between the concrete and the matrix and the cohesion of the concrete itself. Comparative Example 1 is a waterproof component without a reinforcing and densifying component, so it has no reinforcing effect on the strength of the concrete; the hydration aid in Comparative Example 2 improves the early and late strength of the concrete, but because there is no nano-SiO2 / perfluorooctyl acrylate composite emulsion as a cohesion enhancing component, the cohesion of the shotcrete cannot be improved, resulting in a high amount of concrete rebound; Comparative Examples 3 and 4 both improve the early strength of the concrete, but have no effect on the later strength. It can be seen that the anti-corrosion preservative prepared by the present invention has a certain improvement effect on the early strength of the concrete, and does not affect the later strength development. In addition, the rebound rate data shows that the addition of the anti-corrosion preservative of the present invention effectively improves the cohesion of concrete during the rapid setting process, thereby reducing the rebound rate of shotcrete. Combining the data of each embodiment with that of comparative example 1, it can be seen that the nano-SiO2 / perfluorooctyl acrylate composite emulsion plays a key role in reducing rebound, and as the SiO2 content in the emulsion polymerization increases, the cohesion is more significantly improved.

[0092] For the samples prepared in the embodiments of the present invention and the comparative examples, mortar was prepared with 1.2% (solid content) of the adhesive, and the corresponding mixing water amount was deducted according to the solid content of the anti-corrosion preservative, and the performance of the mortar was tested respectively. The test method referred to JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar" and JC / T1011-2021 "Concrete Anti-Corrosion Preservative" as the test standard. The specific performance test results are shown in Table 3.

[0093] Table 3 Concrete resistance to harmful ion corrosion performance

[0094]

[0095] (2) For the samples prepared in the embodiments of the present invention and the comparative examples, concrete was prepared with 1.2% (solid content) of the adhesive as the content. The corresponding amount of mixing water was deducted according to the solid content of the anti-corrosion preservative, and the performance of the concrete was tested respectively. A blank control (blank group) was made with the anti-permeability concrete without adding the anti-corrosion preservative. The mix ratio was referenced to GB / T 31296 "Concrete Anticorrosion and Rust Inhibitors", as shown in Table 4. The capillary water absorption test method was referenced to ASTM C1585-13 "Standard Test Method for Measuring Water Absorption of Hydraulic Cement Concrete", and referenced to GB / T 50082 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete" 6.2 stepwise pressurization method, 0.1 MPa was pressurized to 2.0 MPa for 8 hours, and the penetration height was measured by splitting. The tests were all conducted on 1-day-old concrete. The specific performance test results are shown in Table 5.

[0096] Table 4 Formula of impermeable concrete

[0097]

[0098] Table 5 Concrete waterproof and anti-seepage performance

[0099]

[0100] The following conclusions can be drawn from the above experimental data: the anti-corrosion preservative suitable for shotcrete provided by the present invention is applied to conventional shotcrete, which can significantly reduce the rebound rate of the shotcrete without affecting the early and late strength of the concrete. In addition, the capillary water absorption resistance and pressure water penetration resistance of the concrete to which the anti-corrosion preservative of the present invention is applied can be significantly improved, and the chloride ion diffusion resistance and sulfate resistance are greatly improved.

[0101] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an anti-corrosion preservative for shotcrete, characterized in that: The following steps are involved: Mix water, n-decanoic acid, ammonia water and a hydration aid, then add nano-SiO2 / perfluorooctyl acrylate composite emulsion, stir and mix, and obtain the anti-corrosion preservative for shotcrete; The hydration aid is triethanolamine, triisopropanolamine, diethanol monoisopropanolamine and diethanolamine in a mass ratio of 4:4:4:2; The preparation method of the nano-SiO2 / perfluorooctyl acrylate composite emulsion comprises the following steps: (1) Methyl methacrylate, butyl acrylate and a crosslinking agent are mixed to obtain a core phase monomer; the core phase monomer is placed in an emulsifier aqueous solution to obtain a core monomer pre-emulsion; butyl acrylate, methyl methacrylate and perfluorooctyl acrylate are mixed and placed in an emulsifier aqueous solution to obtain a shell monomer pre-emulsion; (2) mixing a buffer, KH550 modified nano-SiO2, an emulsifier aqueous solution and an initiator aqueous solution, and then adding a core phase monomer to obtain a seed emulsion; adding a core monomer pre-emulsion and an initiator aqueous solution to the seed emulsion, reacting, and obtaining a core phase emulsion; (3) Adding the shell monomer pre-emulsion and the initiator aqueous solution dropwise into the core phase emulsion to react and obtain a nano-SiO2 / perfluorooctyl acrylate composite emulsion.

2. The preparation method according to claim 1, characterized in that: In the core monomer pre-emulsion, the mass ratio of methyl methacrylate, butyl acrylate and cross-linking agent is 5-10:30-40:2-4; and the cross-linking agent is acrylic acid.

3. The preparation method according to claim 1, characterized in that: In the shell monomer pre-emulsion, the mass ratio of the total mass of the methyl methacrylate and perfluorooctyl acrylate to the mass ratio of butyl acrylate is 2-4:1-2; The perfluorooctyl acrylate is one or more of perfluorooctyl ethyl methacrylate, perfluorooctyl ethyl acrylate and perfluorooctanol acrylate.

4. The preparation method according to claim 1, characterized in that: The step (2) is specifically as follows: In a protective atmosphere, 0.1-0.5 parts by weight of a buffer, 5-10 parts by weight of KH550 modified nano-SiO2, an emulsifier aqueous solution and an initiator aqueous solution are mixed, stirred at 80°C at a speed of 100-200 rpm for 20-40 minutes, and then 10 parts by weight of a core phase monomer are added to obtain a seed emulsion; the initiator aqueous solution and a core monomer pre-emulsion are dripped into the seed emulsion, and then the mixture is kept warm at 80°C for 60 minutes to obtain a core phase emulsion; the buffer is sodium bicarbonate.

5. The preparation method according to claim 1, characterized in that: The step (3) is specifically as follows: Add the initiator aqueous solution and the shell monomer pre-emulsion to the core phase emulsion at 80° C., then keep the temperature at 85° C. for 1 hour, adjust the pH value to 8-9, and obtain the nano-SiO2 / perfluorooctyl acrylate composite emulsion.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the water, n-decanoic acid, ammonia water, hydration aid and nano-SiO2 / perfluorooctyl acrylate composite emulsion is 70:5-10:2-4:2-4:

50.

7. An anti-corrosion preservative for shotcrete prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the anti-corrosion preservative for shotcrete according to claim 7 in the field of improving the durability of shotcrete.

Citation Information

Patent Citations

  • Super-early-strength fluoride-free alkali-free liquid accelerator and preparation method thereof

    CN113603384A

  • Polymer as well as preparation method and application thereof

    CN106632886A

  • Preparation method of high-strength alkali-free chloride-free accelerator

    CN109265064A

  • Composition of accelerator for shotcrete

    KR1020040070558A